PERANAN PRAKTIK KERJA INDUSTRI TERHADAP MINAT BEKERJA SISWA KELAS XII JURUSAN PEMASARAN SMK NEGERI BISNIS DAN MANAJEMEN DI KOTA PADANG - Irma Yanti; Syamwil Syamwil; Oknaryana Oknaryana (Jurnal Ecogen, 2018)
Abstract: This study aims to determine the effect of student job training to student work interest in class XII business major in SMK State Businesss and Management in Padang City. The type of this research is descriptive quantitative. This study was taken at SMK State (Business and Management) are SMK Negeri 2 Padang, SMK Negeri 3 Padang and SMK Negeri 4 Padang. The population of this study is 170 students of class XII. Technique of collecting the sample is Proportional Sampling so that it obtained the sample 120 students with Slovin formula. The instrument used is Angket. Analysis simple regression with used SPSS version is used to analysing the data. The result shown that the student job traning is significant influence the interested of student in working of SMK State Business and Management in Padang City. R square of student job training to work interest is 13,1%. The researcher would like to give suggested industry of student job training is relevant with major of the students and the teacher must monitoring when student practice.   Keyword:student job training, work interest